A forma????o continuada de professores do Distrito Federal na EAPE: contextos e concep????es - Dantas, Eriane de Ara??jo (2016)
This study, developed under the Stricto Sensu Post Graduation Program in Education at Universidade Cat??lica de Bras??lia (UCB), discusses the continuous education for teachers of public education in the Federal District (Distrito Federal ??? DF) developed by the Education Professionals Improvement Center (Centro de Aperfei??oamento dos Profissionais de Educa????o ??? EAPE), a Federal District Education Secretary (Secretaria de Estado de Educa????o do Distrito Federal ??? SEDF) unit, existing since 1995. The objective of this study was to analyze the limits and possibilities of this institution in the development of continuous education for teachers. For such, we selected the period from 1995 to 2010, divided into three sessions (1995-1998, 1999- 2002/2003-2006 and 2007-2010), when the administration of DF was conducted by three different governments, with diversified political orientations. For collecting data, we reached for semi-structured interviews and document analysis. The individuals chosen for research were professionals involved with the management of EAPE and the execution of continuing education activities as well as directors of the Federal District Teachers??? Union (Sindicato dos Professores no Distrito Federal ??? Sinpro/DF) in each of the three sessions. Based on data analysis, there were differences noted in what concerns the relevance conferred to continuing education for teachers and to EAPE depending on the political conception of the government in front of the DF administration. We also observed differences in how the continuing education for teachers policy was developed and in whether involved individuals could participate in the formulation of such activities. Throughout its history, EAPE suffered material limitations, such as lack of financial resources and the inadequacy of physical structure for the activities??? execution. In general, EAPE???s actions were also limited due to the absence of closeness of its professionals to the schools, in order to get to know the teachers??? realities and their needs for training; deficiency of teachers??? mobilization strategies to participate on continuing education activities; and lack of effectiveness evaluation of actions developed by the Improvement Center. On the other hand, EAPE may be considered successful in establishing a state policy, which keeps organizing the continuous training of DF education professionals, notwithstanding the influences and alterations it suffers from government changes. We consider that, by overcoming the limitations presented in this study, EAPE will be able to reconstitute itself as a space for the mobilization of teachers and allow a bigger participation of scholars in the elaboration of continuing education principles and activities, in a medium range. We also consider that EAPE will be able to retrieve educational propositions that take the diversity of realities in the DF schooling system and needs of teachers into consideration, investing as well in continuing education activities in the institutions??? spaces.